Summary: Homo, Hunter-Gatherer, Habermas: An Inquiry into Deliberation - van der Does, Ramon (Politics of the Low Countries, 2025)
Many political theorists and pundits deplore the way people talk politics. Arguably, elites and ordinary citizens alike tend to shy away from deliberation, that is, respectful political talk marked by a give-and-take of reasons. A fundamental reason why people supposedly do not deliberate is that it goes against human nature. This view of deliberation vis-à-vis human nature has so far received little scrutiny but has had major implications for how we think about what deliberation requires. It has led some to argue that interventions to promote deliberation are futile (Achen & Bartels, 2016) and others to maintain that deliberation requires institutional tinkering and corrective pedagogy (e.g. Rosenberg, 2014).